Analysis of Mimicry Language in Sabai Sunwoo's Novel as Teaching Material for Strengthening Global Diversity Character - Rahayu; Mukti Widayati; Nurnaningsih (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
The purpose of this research is to analyze the mimicry language in the novel